An interval type-2 fuzzy ELECTRE approach for assessing ballast water treatment systems for ships - Bashan, Veysi; Demirel, Hakan; Kaya, Ahmet (SPRINGER, 2024)
The transportation of dangerous aquatic organisms and pathogens in ballast tanks causes problems on a global scale and therefore, The International Maritime Organization (IMO) has put into force the International Convention for the Control and Management of Ships' Ballast Waters and Sediments. There are many ballast water treatment systems (BWTS) available in the market. The most important issue in the integration of the systems to the ships is to have technical information about the available options and to determine the most suitable solution for the ship among these alternatives. For this, the interested parties need to make an appropriate choice by knowing the features, advantages, and disadvantages of the BWTSs. The main aim of this article is to assess the five types of BWTS technologies that are frequently used and to make an optimum choice by consulting the opinions of experts in the sector. In this context, this study used the fuzzy ELECTRE (ELimination Et Choix Traduisant la REalite') method and proposed a novel approach for handling BWTS selection based upon interval type-2 fuzzy sets. It has been evaluated that a hybrid system in which filtration + ultrasound + ultraviolet (UV) systems can be used together would be more appropriate.
Keywords: Fuzzy ELECTRE; Ballast water treatment; Ship; Filtration; BWTS; ANALYTIC HIERARCHY PROCESS; DECISION-MAKING; CUSTOMER SATISFACTION; MCDM METHOD; EXTENSION; HYDROCYCLONE; TECHNOLOGIES; RADIATION; PREVIEW; Computer Science